1989
DOI: 10.1007/bf01806301
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of androgens on DMBA-induced mammary carcinoma in the rat

Abstract: Constant release of the androgen 5 alpha-dihydrotestosterone (DHT) in ovariectomized rats bearing DMBA-induced mammary carcinoma caused a marked inhibition of tumor growth induced by 17 beta-estradiol (E2). That DHT acts through interaction with the androgen receptor is supported by the finding that simultaneous treatment with the antiandrogen Flutamide completely prevents DHT action. Particularly illustrative of the potent inhibitory effect of DHT on tumor growth are the decrease by DHT of the number of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…To investigate the possibility that DHEA and its metabolites could have a preventive effect on the development of mammary carcinoma, we have studied the effect of increasing circulating levels of DHEA constantly released from Silastic brand implants on the development of mammary carcinoma induced by DMBA in the rat. The DMBA-induced mammary carcinoma in the rat has been widely used as a model of hormone-sensitive breast cancer in women (242,256,257).…”
Section: Inhibitory Effect Of Dhea On Breast Cancermentioning
confidence: 99%
“…To investigate the possibility that DHEA and its metabolites could have a preventive effect on the development of mammary carcinoma, we have studied the effect of increasing circulating levels of DHEA constantly released from Silastic brand implants on the development of mammary carcinoma induced by DMBA in the rat. The DMBA-induced mammary carcinoma in the rat has been widely used as a model of hormone-sensitive breast cancer in women (242,256,257).…”
Section: Inhibitory Effect Of Dhea On Breast Cancermentioning
confidence: 99%
“…Treatment with testosterone alone also induced mammary tumors in the same rat strain (7,8). In contrast, inhibitory effects of androgens on the development (9) or progression (10) of dimethylbenz(a)anthracene-induced mammary tumors in female rats have been reported. Occasional enhancement of tumor growth was observed in some experiments in which moderate or very high doses of androgen were used (reviewed in Ref.…”
Section: Introductionmentioning
confidence: 90%
“…The two largest perpendicular diameters of each tumor were measured with calipers and the product of these diameters was used to estimate tumor size [17]. Tumor size measured on the day of OVX or on the day before starting treatment was taken as 100%.…”
Section: Treatmentmentioning
confidence: 99%
“…[17] have shown that constant release of the androgen DHT in ovariectomized rats bearing DMBA-induced mammary carcinoma caused a marked inhibition of tumor growth induced by 17[~-estradiol (E2). That DHT acts through interaction with the androgen receptor is supported by the finding that simultaneous treatment with the antiandrogen Flutamide completely prevented DHT action.…”
Section: Growth Inhibition Of Rat Mammary Tumorsmentioning
confidence: 99%